Advances of orbital gas tungsten arc welding for Brazilian space applications - experimental setup - Garcia,José A. Orlowski de (2010)
Abstract: The present work describes details of the several steps of the technology involved for the orbital Gas Tungsten Arc Welding (GTAW) process of pure commercially titanium tubes. These pieces will be used to connect the several components of the propulsion system of the China-Brazilian Satellite CBERS, and is part of the Brazilian aerospace industry development. The implantation involved the steps of environment control; cut and facing of the base metal; cleaning procedures; piece alignment; choice of the type, geometry and installation of the tungsten electrode; system for the pressure of the purge gas; manual tack welding; choice of the welding parameters; and, finally, the qualification of welding procedures. Three distinct welding programs were studied, using pulsed current with increasing speed, continuous current and pulsed current with decreasing amperage levels. The results showed that the high quality criteria required to the aerospace segment is such that usual welding operations must be carefully designed and executed. The three welding developed programs generated welds free of defects and with adequate morphology, allowing to select the condition that better fits the Brazilian aerospace segment, and to be implanted in the welding of the CBERS Satellite Propulsion System.